P226 Combined analysis of two randomized controlled trials of budesonide/formoterol reliever therapy in adults with mild asthma. (12th November 2019) - Weatherall, M; Holliday, M; Baggott, C; Braithwaite, I; Fingleton, J; Hardy, J; Hancox, RJ; Harrison, T; Papi, A; Pavord, I; Reddel, HK; Williams, M; et al.
Abstract : Background: This analysis combines two randomised controlled trials with similar protocols recruiting adults with asthma to explore the effects of covariates on the comparison of combination inhaled corticosteroid (ICS)/fast-onset long-acting beta-agonist (LABA) as reliever therapy versus maintenance ICS plus short-acting beta-agonist (SABA) reliever therapy. Methods: A combined individual participant analysis of the Novel START (ACTRN12615000999538) and PRACTICAL (ACTRN1261000377437) studies. These were 52-week, open-label, parallel-group, randomised controlled trials in adults with asthma. Novel START randomised 675 adults using only as-needed SABA to : salbutamol pMDI 100µg two inhalations as-needed for symptom relief, or budesonide Turbuhaler 200µg one inhalation twice daily plus salbutamol pMDI 100µg two inhalations as-needed, or budesonide/formoterol Turbuhaler 200/6µg one inhalation as-needed. PRACTICAL randomised 890 adults using as-needed SABA for symptom relief, with or without maintenance ICS to: budesonide-formoterol Turbuhaler 200/6 one inhalation as-needed; or budesonide Turbuhaler 200µg one inhalation twice daily plus terbutaline Turbuhaler 500µg as-needed. The analysis compared as-needed budesonide-formoterol with maintenance budesonide plus SABA reliever therapy. The primary outcome was the rate of severe exacerbations per participant per year: i.e. hospital/emergency department systemic corticosteroid treatment or the use of at least 3 days of systemic corticosteroids for asthma in the community. Novel START participants were withdrawn if they experienced a severe exacerbation. The other outcomes were moderate or severe exacerbations, and the Asthma Control Questionnaire (ACQ-5) score. Covariates were: age, sex, ethnicity, smoking status, baseline SABA use, baseline ICS use ever, severe exacerbation in previous 12 months, ACQ-5, blood eosinophil count, and FeNO. Results: The severe exacerbation rate was 0.096 per patient-year for as-needed budesonide/formoterol and 0.150 for maintenance budesonide plus as-needed SABA; adjusted relative rate 0.63 (95% CI: 0.45 to 0.89), P=0.01. The adjusted relative rate of any exacerbation was 0.66 (95% CI: 0.49 to 0.88), P<0.001. ACQ-5 did not differ between treatments. There was no evidence of any sub-group differences in response to as-needed budesonide/formoterol versus budesonide maintenance. Conclusions: The rate of severe exacerbations was lower for as-needed budesonide/formoterol therapy compared to budesonide plus as-needed SABA. No evidence of sub-group differences suggests the findings are generalisable across the spectrum of mild asthma in adults.